Health management trends: The Internet of Things as a modernization and care tool - Vidal, Emerson Pessoa; De Liberal, Márcia Mello Costa; Zucchi, Paola (International Journal for Innovation Education and Research, 2020)
The modernization of health institutions is one of the biggest trends of our time. Part of the 4th industrial revolution, the Internet of Things, that allows a more personalized care and greater appreciation for the patient, can be a reality that is in the process of being consolidated worldwide. In Brazil, through the promulgation of decree number 9.854 of June 26th of 2019, the democratization and popularization of these technologies have started. This integrative review intends to verify the introduction of IoTs in the Brazilian scenario by investigating the potential as well as the weaknesses of this new technology. The research suggests that IoTs are a unique content that may improve productivity and process efficiencies but are still permeated by caveats that indicate system deficiencies and the need of further studies.